Review on Clinical Trials of Black Seed (Nigella sativa ) and Its Active Constituent, Thymoquinone - Alireza Tavakkoli; Vahid Mahdian; Bibi Marjan Razavi; Hossein Hosseinzadeh (Korean Pharmacopuncture Institute, 2017)
Objectives: Nigella sativa (black seed or black cumin), which belongs to the Ranunculacea family, is an annual herb with many pharmacological properties. Among its many active constituents, thymoquinone (TQ) is the most abundant constituent of the volatile oil of Nigella sativa (N. sativa) seeds, and it is the constituent to which most properties of this herb are attributed. Methods: PubMed-Medline, Scopus, and Web of Science databases were searched to identify randomized control trials (RCTs) investigating the therapeutic effects of N. sativa and/or TQ. In this review, we investigated the clinical uses of N. sativa and TQ in the prevention and the treatment of different diseases and morbidity conditions in humans. Results: Black seed and TQ are shown to possess multiple useful effects for the treatment of patients with several diseases, such as inflammatory and auto-immune disorders, as well as metabolic syndrome. Also, other advantages, including antimicrobial, anti-nociceptive and anti-epileptic properties, have been documented. The side effects of this herbal medicine appear not to be serious, so it can be applied in clinical trials because of its many advantages. Conclusion: Some effects of N. sativa, such as its hypoglycemic, hypolipidemic and bronchodilatory effects, have been sufficiently studied and are sufficiently understood to allow for the next phase of clinical trials or drug developments. However, most of its other effects and applications require further clinical and animal studies.